Pengaruh Struktur Modal Terhadap Tax Avoidance dengan Struktur Kepemilikan Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022 - Jelita Prakasita Handi Dhaneswara; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of capital structure on tax avoidance by using ownership structure, financial performance and company characteristics as intervening variables. This research is a descriptive quantitative research using a Smart PLS4 based statistical data analysis method, using a purposive sampling technique where the researcher chose to focus the research on pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange in 2020 - 2022. Resulting in 9 hypotheses and one of them shows positive and significant influence, namely the influence of Capital Structure on Ownership structure.